Method for evaluating volume change rate of martensitic steel after heat treatment

The volume change rate of martensite steel after heat treatment was measured through XRD test, which solved the problem that was difficult to accurately determine in the prior art, and realized the accurate evaluation of the volume change of martensite steel and the prediction of material stability, and improved the ability to regulate material dimensional stability.

CN119880968APending Publication Date: 2025-04-25HENAN UNIV OF SCI & TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411987694.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to accurately determine the volume change rate of martensite steel after heat treatment, which limits the in-depth study of material dimensional stability.

Method used

The diffraction peak intensity of martensite and austenite in the heat treatment sample was determined by XRD test, the volume percentage of austenite and martensite was calculated, and the volume change rate of martensite steel was calculated based on the lattice constant.

Benefits of technology

It can accurately assess the volume changes of martensite steel after heat treatment, initially predict the stability of the material, improve the ability to regulate the dimensional stability of the material, and avoid the dimensional instability of the material in various environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119880968A_ABST
    Figure CN119880968A_ABST
Patent Text Reader

Abstract

The invention relates to a method for evaluating the volume change rate of martensitic steel after heat treatment, a martensitic steel sample is subjected to heat treatment, the sample subjected to heat treatment is subjected to XRD (X-Ray Diffraction) test, and experimental parameters of the XRD test comprise diffraction peak intensity of martensite and austenite in the sample subjected to heat treatment; calculating the volume percentage V 'gamma of austenite in the heat-treated sample and the volume percentage V' alpha of martensite in the heat-treated sample; and substituting the V 'gamma, the V' alpha, the martensite lattice constant a alpha and the austenite lattice constant a gamma into a formula # imgabs0 # to calculate the volume change rate of the martensite steel after heat treatment. According to the method, the volume change condition of the martensitic steel after heat treatment can be obtained, the stability of the material after heat treatment is preliminarily pre-judged, the regulation and control capability on the dimensional stability of the material is improved, and the influence of different heat treatment processes on the dimensional stability of the martensitic steel is effectively evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material dimensional stability evaluation, and in particular relates to a method for evaluating the volume change rate of martensitic steel after heat treatment. Background Art

[0002] At present, the research and development of martensitic steel in my country is still in the development stage. At present, the performance pursuit of martensitic steel is mainly mechanical properties (elastic modulus, strong plasticity, toughness, hardness, cold bending performance, fatigue performance). However, with the in-depth research and exploration of science and technology in the heavy industry and aviation fields, the material is required to have more outstanding mechanical properties while also requiring long-term high precision and high availability. The dimensional stability of martensitic steel is one of the main factors affecting the service life of the workpiece. In order to ensure the accuracy of the material while improving the life of the material, more stringent requirements are placed on the dimensional stability of the material. Dimensional stability originally refers to the ability of a material to maintain its initial size and shape without change over a period of time under a certain environment. The study of material dimensional stability is the irreversible micro-deformation that occurs after storage or service for a short period of time, ranging from a few days to a few years or more than ten years.

[0003] Martensitic steel has been widely used in high-end fields (space engineering, military weapons, nuclear industry, etc.). However, its application in extreme environments is still in the exploratory stage, and dimensional stability is a necessary performance that determines whether the material can be used for a long time in various extreme environments. Good dimensional stability plays a decisive role in improving the service life, safety, reliability and operating efficiency of equipment under harsh working conditions. Typical products such as aerospace rocket nozzles, armor-piercing shells in the military industry, the first plasma-facing wall in nuclear fusion reactors, and die-casting molds in the metallurgical industry are used in high-temperature fields. Rocket nozzles require that the material does not recrystallize at high temperatures and has excellent high-temperature strength, plasticity and dimensional stability; the first plasma-facing wall on the nuclear fusion reactor has extremely high requirements for safety and reliability in use, requiring the material to have not only good high-temperature resistance and radiation resistance, but also excellent high-temperature organizational stability and high-temperature strength. Dimensional stability is an urgent need for extreme environment engineering equipment and represents the development trend of high-end martensitic steel.

[0004] However, the research on the dimensional stability of martensitic steel is relatively superficial. The current mainstream dimensional stability test methods are mainly macroscopic test methods (hot and cold cycle method, triangular ring method, etc.). These methods cannot accurately measure the volume change rate of martensitic steel after heat treatment, and are not conducive to intuitively understanding the impact of different heat treatment processes on the volume change of martensitic steel, which limits the deeper research on the dimensional stability of the material. Summary of the invention

[0005] The purpose of the present invention is to provide a method for evaluating the volume change rate of martensitic steel after heat treatment. The volume change of martensitic steel after heat treatment can be obtained through the size of the volume change rate, and the stability of the material after heat treatment can be preliminarily predicted, which can improve the ability to regulate the dimensional stability of the material and help avoid dimensional instability of the material in various application environments to a certain extent.

[0006] The present invention is specifically implemented by the following technical scheme. According to a method for evaluating the volume change rate of martensitic steel after heat treatment proposed by the present invention, the method comprises the following steps:

[0007] (1) The martensitic steel sample is heat treated. The unheat treated sample is full martensitic steel. After heat treatment, austenite appears in the sample.

[0008] (2) Performing XRD test on the heat-treated sample. The experimental parameters of the XRD test include the diffraction peak intensity of martensite and austenite in the heat-treated sample Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211), wherein α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensity of the austenite (200) crystal plane, Iγ(220) represents the diffraction peak intensity of the austenite (220) crystal plane, Iγ(311) represents the diffraction peak intensity of the austenite (311) crystal plane, Iα(200) represents the diffraction peak intensity of the martensite (200) crystal plane, and Iα(211) represents the diffraction peak intensity of the martensite (211) crystal plane; calculating the volume percentage V' of austenite in the heat-treated sample γ and the volume percentage of martensite in the sample after heat treatment V' α ;

[0009] (3) The volume percentage of austenite in the heat treated sample V' γ , Volume percentage of martensite in the sample after heat treatment V' α , martensite lattice constant a α , austenite lattice constant a γ Substitute into formula (2) The volume change rate of martensitic steel after heat treatment is calculated;

[0010] Among them, ΔV% is the volume change rate of martensitic steel after heat treatment, V' α is the volume percentage of martensite in the sample after heat treatment, V' γ is the volume percentage of austenite in the sample after heat treatment, a α is the martensite lattice constant, a γ is the austenite lattice constant.

[0011] Furthermore, during the XRD test, the metal target used was a Co target.

[0012] Furthermore, the volume percentage V' of austenite in the heat-treated sample was calculated according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ According to formula (1) V' γ +V' α = 100% The volume percentage of martensite in the sample after heat treatment is calculated as V' α , the martensite lattice constant a is obtained according to the standard PDF card in the International Diffraction Data Center database α and austenite lattice constant a γ .

[0013] Furthermore, according to the five-wire six-pair method in YB / T 5338-2019, according to formula (3) Calculated volume percentage of austenite in the heat treated sample V' γ , in formula (3), V' γ is the volume percentage of austenite in the sample after heat treatment, V c Indicates the volume percentage of the total amount of carbide phase in the sample. The carbon content of the martensitic steel used in the experiment is less than 0.01%. c Ignore, so V c =0; Indicates the martensite phase in the sample after heat treatment (hkl) i The diffraction peak intensity of the crystal plane; Indicates the austenite phase in the sample after heat treatment (hkl) i Diffraction peak intensity of crystal plane; G represents austenite phase (hkl) i Crystal plane and martensite phase (hkl) i The ratio of intensity-related factors corresponding to the crystal plane.

[0014] Furthermore, the ratio of the diffraction peak intensity of martensite to austenite in the heat treated sample is include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V' once γ , a total of 6 V' γ value, and then calculate the 6 V' γ The arithmetic mean of the values ​​is the volume percentage V' of austenite in the sample after heat treatment. γ .

[0015] In the aforementioned method for evaluating the volume change rate of martensitic steel after heat treatment, step (1) uses a resistance furnace with a model of BSK-83 and a rated power of 9KW to heat treat the martensitic steel sample.

[0016] The above-mentioned method for evaluating the volume change rate of martensitic steel after heat treatment, step (1) heat treats the full martensitic steel sample in a resistance furnace with a model of BSK-83 and a rated power of 9KW, and the specific operation of the heat treatment includes: heating the resistance furnace to 1000°C at a heating rate of 10°C / min, keeping the sample at 1000°C for 60 minutes, and after completion, taking out the sample and cooling it to room temperature in the air; then placing the sample in the resistance furnace, heating the resistance furnace from room temperature to 750°C at a heating rate of 10°C / min, keeping the sample at 750°C for 60 minutes, and after completion, taking out the sample and cooling it to room temperature in the air to obtain a heat-treated sample.

[0017] The above-mentioned method for evaluating the volume change rate of martensitic steel after heat treatment comprises the following steps: (1) heat treating a full martensitic steel sample in a resistance furnace of model BSK-83 and rated power 9 kW, wherein the specific operation of the heat treatment comprises: heating the resistance furnace to 1000°C at a heating rate of 10°C / min, keeping the sample at 1000°C for 60 minutes, taking out the sample and cooling it to room temperature in air; then placing the sample in the resistance furnace again, heating the resistance furnace from room temperature to 750°C at a heating rate of 10°C / min, The sample was kept at 750°C for 60 minutes, and then taken out and placed in the air to cool to room temperature; then the sample was immersed in -196°C liquid nitrogen for 120 minutes, and then taken out and placed in the air to recover to room temperature; finally, the sample was placed in the resistance furnace again, and the resistance furnace was heated from room temperature to 500-600°C at a heating rate of 10°C / min, and the sample was kept at 500-600°C for 180 minutes for aging treatment. After completion, the sample was taken out and placed in the air to cool to room temperature to obtain the heat-treated sample.

[0018] Furthermore, the temperature of the aging treatment is 525°C or 575°C.

[0019] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages:

[0020] The present invention calculates the volume percentage V' of austenite in the sample after heat treatment based on the phase transformation and corresponding dimensional change of martensitic steel during heat treatment. γ and the volume percentage of martensite in the sample after heat treatment V' α, the process parameters such as the volume percentage of martensite and the volume percentage of austenite in the sample after heat treatment are brought into the volume change rate calculation model to obtain the volume change rate of martensitic steel after heat treatment. The volume change of martensitic steel after heat treatment can be obtained through the size of the volume change rate, so as to preliminarily predict the stability of the material after heat treatment. By evaluating the volume change rate, the ability to regulate the dimensional stability of the material can be effectively improved, assisting the existing macroscopic dimensional stability test method, and to a certain extent, helping to avoid the dimensional instability of the material in various environments. The evaluation method of the present invention can be applied in both room temperature environments and low temperature extreme environments, can reduce the cost of experimental design and prediction, effectively guide the manufacturing process, avoid causing dimensional instability of the material, and has high flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic diagram of the heat treatment process in Examples 1 to 3 of the present invention;

[0022] Figure 2 1 is the microstructure diagram (OM diagram) of the unheat-treated full martensitic steel sample of the present invention and the sample after heat treatment by the process of Examples 1 to 3 under an optical microscope, wherein (a) represents the unheat-treated full martensitic steel sample, and (b), (c), and (d) correspond to the samples after heat treatment by the process of Examples 1, 2, and 3, respectively;

[0023] Figure 3 3 are SEM images of the unheat-treated full martensitic steel sample of the present invention and the samples after heat treatment by the processes of Examples 1 to 3, wherein (a) represents the unheat-treated full martensitic steel sample, and (b), (c), and (d) correspond to the samples after heat treatment by the processes of Examples 1, 2, and 3, respectively. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention provides a method for evaluating the volume change rate of martensitic steel after heat treatment, comprising the following steps:

[0026] (1) A resistance furnace with a model of BSK-83 and a rated power of 9 kW was used to heat treat the martensitic steel sample. The unheat-treated sample was full martensitic steel. After heat treatment, the martensite phase transformed into the austenite phase, and the austenite phase appeared in the sample.

[0027] (2) X-ray diffraction (XRD) test was performed on the heat-treated sample. During the test, Co target was used as the metal target. The experimental parameters of the XRD test included the diffraction peak intensity of martensite and austenite in the heat-treated sample, Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211), wherein α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensity of the austenite (200) crystal plane, Iγ(220) represents the diffraction peak intensity of the austenite (220) crystal plane, Iγ(311) represents the diffraction peak intensity of the austenite (311) crystal plane, Iα(200) represents the diffraction peak intensity of the martensite (200) crystal plane, and Iα(211) represents the diffraction peak intensity of the martensite (211) crystal plane. The volume percentage V' of austenite in the heat-treated sample was calculated according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ According to formula (1) V' γ +V' α = 100% The volume percentage of martensite in the sample after heat treatment is calculated as V' α , the martensite lattice constant a is obtained according to the standard PDF card in the International Diffraction Data Center database α and austenite lattice constant a γ .

[0028] (3) The volume percentage of austenite in the heat treated sample V' γ , Volume percentage of martensite in the sample after heat treatment V' α , martensite lattice constant a α , austenite lattice constant a γ Substitute into formula (2) The volume change rate of the full martensitic steel after heat treatment is calculated; where ΔV% is the volume change rate of the full martensitic steel after heat treatment, V' α is the volume percentage of martensite in the sample after heat treatment, V' γ is the volume percentage of austenite in the sample after heat treatment, a α is the martensite lattice constant, a γ is the austenite lattice constant.

[0029] Furthermore, the volume percentage of austenite in the sample after heat treatment V' γ , Volume percentage of martensite in the sample after heat treatment V' α The calculation method is as follows:

[0030] According to the five-line six-pair method in YB / T 5338-2019, according to formula (3) Calculated volume percentage of austenite in the heat treated sample V' γ, in formula (3), V' γ is the volume percentage of austenite in the sample after heat treatment, V c Indicates the volume percentage of the total amount of carbide phase in the sample (the carbon content of the experimental steel is less than 0.01%, so V c can be ignored, and V c =0), Indicates the martensite phase in the sample after heat treatment (hkl) i The diffraction peak intensity of the crystal plane; Indicates the austenite phase in the sample after heat treatment (hkl) i Diffraction peak intensity of crystal plane; G represents austenite phase (hkl) i Crystal plane and martensite phase (hkl) i The ratio of the intensity-related factors corresponding to the crystal plane is The abbreviation of G is different according to different diffraction. The G values ​​of different diffraction line pairs are shown in Table 1.

[0031] Table 1. G values ​​of different diffraction line pairs (Co target)

[0032] G (200)γ (220)γ (311)γ (200)α 2.46 1.32 1.78 (211)α 1.21 0.65 0.87

[0033] The ratio of the diffraction peak intensity of martensite to austenite in the sample after heat treatment include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V' once γ , a total of 6 V' γ value, and then calculate the 6 V' γ The arithmetic mean of the values ​​is the volume percentage V' of austenite in the sample after heat treatment. γ . V' γ Substitute into formula (1) V' γ +V' α = 100% The volume percentage of martensite in the sample after heat treatment is calculated as V' α .

[0034] Martensitic steel undergoes phase transformation during heat treatment, causing volume changes, and the volume change rate is:

[0035]

[0036] Where V 马 、V' 马 、V' 奥 They are the volume of martensite in the sample before heat treatment, the volume of martensite in the sample after heat treatment, and the volume of austenite in the sample after heat treatment.

[0037] V 马 、V' 马 、V' 奥 It can be calculated by the number of unit cells × unit cell volume (V = N × a 3 ) is obtained, that is

[0038]

[0039]

[0040] therefore,

[0041]

[0042] Where N α , N' α , N' γ are the unit cell number of martensite before heat treatment, the unit cell number of martensite after heat treatment, and the unit cell number of austenite after heat treatment. Martensite is a body-centered cubic structure, and austenite is a face-centered cubic structure, containing 2 and 4 atoms respectively. The total number of atoms in the sample before and after heat treatment remains unchanged. Therefore, the following relationship exists during the martensite-austenite phase transformation: N α -N' α =2N' γ ,Right now

[0043]

[0044] Substituting formula (8) and formula (9) into formula (10), we get:

[0045]

[0046] The ratio of the volume of austenite to the volume of martensite in the heat treated sample is equal to the ratio of the volume percentage of austenite to the volume percentage of martensite in the heat treated sample, that is:

[0047]

[0048] Substituting formula (12) into formula (11), we get:

[0049]

[0050] Substituting formula (13) into formula (4) yields:

[0051]

[0052] In formula (2), ΔV% is the volume change rate of the fully martensitic steel sample after heat treatment, V' α is the volume percentage of martensite in the sample after heat treatment, V' γis the volume percentage of austenite in the sample after heat treatment, a α is the martensite lattice constant, a γ is the austenite lattice constant.

[0053] The following is a detailed description with specific embodiments:

[0054] Embodiment 1:

[0055] (1) Taking the unheat-treated sample as the benchmark, the unheat-treated sample is full martensitic steel. After the full martensitic steel is heat-treated, austenite appears in the sample;

[0056] Specific operation of heat treatment: heat treatment is carried out on the full martensitic steel sample in a BSK-83 resistance furnace with a rated power of 9KW. The resistance furnace is heated to 1000℃ at a heating rate of 10℃ / min, and the sample is kept at 1000℃ for 60min. After completion, the sample is taken out and cooled to room temperature in the air; then the sample is placed in the resistance furnace again, and the resistance furnace is heated from room temperature to 750℃ at a heating rate of 10℃ / min. The sample is kept at 750℃ for 60min. After completion, the sample is taken out and cooled to room temperature in the air to obtain the heat-treated sample.

[0057] (2) The heat-treated sample was subjected to XRD test. During the test, the metal target used was Co target. The experimental parameters of the XRD test included the diffraction peak intensities of martensite and austenite Iγ(200), Iγ(220), Iγ(311), Iα(200), and Iα(211). The test results were: Iγ(200)=19695, Iγ(220)=34258, Iγ(311)=18160, Iα(200)=63597, and Iα(211)=119421. The above data were converted into the five-line six-pair method in the national standard YB / T 5338-2019 according to formula (3): Calculate the volume percentage V' of austenite in the sample after heat treatment γ =18.62%, according to formula (1) V' γ +V' α = 100% The volume percentage of martensite in the sample after heat treatment is calculated as V' α =81.38%, then According to the standard PDF card in the International Diffraction Data Center database, the martensite lattice constant a is obtained: α =2.873, austenite lattice constant a γ =3.593, that is

[0058] (3) Substitute into formula (2) The volume change rate of the fully martensitic steel after heat treatment was calculated to be ΔV% = -0.408%.

[0059] Example 2

[0060] The specific operation of the heat treatment is as follows: the full martensitic steel sample is heat treated in a BSK-83 resistance furnace with a rated power of 9KW, the resistance furnace is heated to 1000°C at a heating rate of 10°C / min, the sample is kept at 1000°C for 60 minutes, and after completion, the sample is taken out and placed in the air to cool to room temperature; then the sample is placed in the resistance furnace again, the resistance furnace is heated from room temperature to 750°C at a heating rate of 10°C / min, the sample is kept at 750°C for 60 minutes, and after completion, the sample is taken out and placed in the air to cool to room temperature; then the sample is immersed in -196°C liquid nitrogen for 120 minutes, and after completion, the sample is taken out and placed in the air to recover to room temperature; finally, the sample is placed in the resistance furnace again, the resistance furnace is heated from room temperature to 525°C at a heating rate of 10°C / min, the sample is kept at 525°C for 180 minutes (aging treatment), and after completion, the sample is taken out and placed in the air to cool to room temperature to obtain a heat-treated sample.

[0061] According to the standard PDF card in the International Diffraction Data Center database, the martensite lattice constant a is obtained: α =2.873, austenite lattice constant a γ =3.593, that is The remaining operations and calculation process are the same as in Example 1, and V' is obtained. γ =43.62%, V' α =56.38%, The volume change rate of the full martensitic steel after heat treatment in this embodiment is ΔV%=-0.951%.

[0062] Example 3

[0063] The specific operation of the heat treatment is as follows: the full martensitic steel sample is heat treated in a BSK-83 resistance furnace with a rated power of 9KW, the resistance furnace is heated to 1000°C at a heating rate of 10°C / min, the sample is kept at 1000°C for 60 minutes, and after completion, the sample is taken out and placed in the air to cool to room temperature; then the sample is placed in the resistance furnace again, the resistance furnace is heated from room temperature to 750°C at a heating rate of 10°C / min, the sample is kept at 750°C for 60 minutes, and after completion, the sample is taken out and placed in the air to cool to room temperature; then the sample is immersed in -196°C liquid nitrogen for 120 minutes, and after completion, the sample is taken out and placed in the air to recover to room temperature; finally, the sample is placed in the resistance furnace again, the resistance furnace is heated from room temperature to 575°C at a heating rate of 10°C / min, the sample is kept at 575°C for 180 minutes (aging treatment), and after completion, the sample is taken out and placed in the air to cool to room temperature to obtain a heat-treated sample.

[0064] According to the standard PDF card in the International Diffraction Data Center database, the martensite lattice constant a is obtained: α =2.873, austenite lattice constant a γ =3.593, that is The remaining operations and calculation process are the same as in Example 1, and V' is obtained. γ =36.14%, V' α =63.86%, The volume change rate of the full martensitic steel after heat treatment in this embodiment is ΔV%=-0.789%.

[0065] The diffraction peak intensities measured by XRD under different heat treatment processes in Examples 1 to 3 are shown in Table 2, and the volume change rates of martensitic steel after heat treatment calculated under different heat treatment processes in Examples 1 to 3 are shown in Table 3.

[0066] Table 2. Diffraction peak intensity of different heat treatment processes measured by XRD

[0067]

[0068] Table 3. Volume change rate of samples obtained by different heat treatment processes

[0069]

[0070] Figure 1 It is a schematic diagram of the heat treatment process of Examples 1 to 3 of the present invention.

[0071] Figure 2It is the organization diagram (OM diagram) of the unheat-treated full martensitic steel sample of the present invention and the sample after heat treatment by the process of Examples 1 to 3 under the optical microscope; wherein, (a), (b), (c), and (d) respectively represent the unheat-treated full martensitic steel sample, the sample after heat treatment according to the process of Example 1, the sample after heat treatment according to the process of Example 2, and the sample after heat treatment according to the process of Example 3. It can be seen that compared with the unheat-treated full martensitic steel sample, the austenite content in the sample increases after heat treatment, and the microstructure of the sample changes. In addition, Figure 2 The microstructures of (b), (c), and (d) are obviously different, which is due to the different austenite contents in the samples obtained by different heat treatment processes.

[0072] Figure 3 : is the SEM image of the unheat-treated full martensitic steel sample of the present invention and the sample after heat treatment by the process of Examples 1 to 3, wherein: Figure 3 (a), (b), and (c) represent the unheat-treated full martensitic steel sample, the sample heat-treated according to the process of Example 1, the sample heat-treated according to the process of Example 2, and the sample heat-treated according to the process of Example 3, respectively. It can be seen that the SEM images of the heat-treated sample and the unheat-treated full martensitic steel sample are quite different. This is because the martensite phase transforms to the austenite phase after the heat treatment, making its microstructure different. In addition, Figure 3 The SEM images of (b), (c), and (d) are also quite different, and the microstructures are obviously different. This is because the austenite content in the samples obtained by different heat treatment processes is different.

[0073] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for evaluating the volume change rate of martensitic steel after heat treatment, characterized in that The following steps are involved: (1) The martensitic steel sample is heat treated. The unheat treated sample is full martensitic steel. After heat treatment, austenite appears in the sample. (2) Performing XRD test on the heat-treated sample, the experimental parameters of the XRD test include the diffraction peak intensity of martensite and austenite in the heat-treated sample Iγ(200), Iγ(220), Iγ(311), Iα(200), Iα(211), where α represents martensite and γ represents austenite; Iγ(200) represents the diffraction peak intensity of the austenite (200) crystal plane, Iγ(220) represents the diffraction peak intensity of the austenite (220) crystal plane, Iγ(311) represents the diffraction peak intensity of the austenite (311) crystal plane, Iα(200) represents the diffraction peak intensity of the martensite (200) crystal plane, and Iα(211) represents the diffraction peak intensity of the martensite (211) crystal plane; calculating the volume percentage V of austenite in the heat-treated sample γ , and the volume percentage of martensite in the sample after heat treatment V α , ; (3) The volume percentage of austenite in the heat treated sample V γ , , Volume percentage of martensite in the sample after heat treatment V α , , martensite lattice constant a α , austenite lattice constant a γ Substitute into formula (2) The volume change rate of martensitic steel after heat treatment is calculated; Among them, ΔV% is the volume change rate of martensitic steel after heat treatment, V α , is the volume percentage of martensite in the sample after heat treatment, V γ , is the volume percentage of austenite in the sample after heat treatment, a α is the martensite lattice constant, a γ is the austenite lattice constant.

2. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 1, characterized in that During the XRD test, the metal target used was Co target.

3. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 1, characterized in that The volume percentage V of austenite in the heat-treated sample is calculated according to the five-line six-pair method in the ferrous metallurgy industry standard YB / T 5338-2019 of the People's Republic of China. γ , According to formula (1) V γ , +V α , =100% The volume percentage of martensite in the sample after heat treatment is calculated as V α , , the martensite lattice constant a is obtained according to the standard PDF card in the International Diffraction Data Center database α and austenite lattice constant a γ .

4. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 1 or 3, characterized in that According to the five-wire six-pair method in YB / T 5338-2019, according to formula (3) Calculated volume percentage of austenite in the heat treated sample V γ , In formula (3), V γ , is the volume percentage of austenite in the sample after heat treatment, V c Indicates the volume percentage of the total amount of carbide phase in the sample. The carbon content of the martensitic steel used in the experiment is less than 0.01%. c Ignore, so V c =0; Indicates the martensite phase in the sample after heat treatment (hkl) i The diffraction peak intensity of the crystal plane; Indicates the austenite phase in the sample after heat treatment (hkl) i Diffraction peak intensity of crystal plane; G represents austenite phase (hkl) i Crystal plane and martensite phase (hkl) i The ratio of intensity-related factors corresponding to the crystal plane.

5. The method for evaluating the volume change rate of martensitic steel after heat treatment as claimed in claim 4, characterized in that The ratio of the diffraction peak intensity of martensite to austenite in the sample after heat treatment include Each pair Substitute the value of and the corresponding G value into formula (3) Calculate V once γ , , a total of 6 V γ , value, and then calculate the 6 V γ , The arithmetic mean of the values ​​is the volume percentage V of austenite in the sample after heat treatment. γ , .

6. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 1, characterized in that Step (1) uses a resistance furnace with a model of BSK-83 and a rated power of 9 kW to heat treat the martensitic steel sample.

7. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 1 or 6, characterized in that Step (1) heat-treating the full martensitic steel sample in a resistance furnace with a model of BSK-83 and a rated power of 9 kW. The specific operation of the heat treatment includes: heating the resistance furnace to 1000°C at a heating rate of 10°C / min, keeping the sample at 1000°C for 60 minutes, and after completion, taking out the sample and cooling it to room temperature in the air; then placing the sample in the resistance furnace again, heating the resistance furnace from room temperature to 750°C at a heating rate of 10°C / min, keeping the sample at 750°C for 60 minutes, and after completion, taking out the sample and cooling it to room temperature in the air to obtain a heat-treated sample.

8. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 1 or 6, characterized in that Step (1) heat treating the full martensitic steel sample in a resistance furnace with a model of BSK-83 and a rated power of 9KW, wherein the specific operation of the heat treatment comprises: heating the resistance furnace to 1000°C at a heating rate of 10°C / min, keeping the sample at 1000°C for 60 minutes, and after completion, taking out the sample and cooling it to room temperature in the air; then placing the sample in the resistance furnace again, heating the resistance furnace from room temperature to 750°C at a heating rate of 10°C / min, keeping the sample at 750°C for 60 minutes, and after completion, taking out the sample and cooling it to room temperature in the air; then immersing the sample in liquid nitrogen at -196°C for 120 minutes, and after completion, taking out the sample and restoring it to room temperature in the air; finally, placing the sample in the resistance furnace again, heating the resistance furnace from room temperature to 500-600°C at a heating rate of 10°C / min, keeping the sample at 500-600°C for 180 minutes for aging treatment, and after completion, taking out the sample and cooling it to room temperature in the air to obtain a heat-treated sample.

9. The method for evaluating the volume change rate of martensitic steel after heat treatment according to claim 8, characterized in that The temperature of the aging treatment is 525°C or 575°C.

Citation Information

Cited By

  • Method, system, equipment and medium for quantitatively evaluating austenite stability of steel

    CN122063245A

  • Method, system, apparatus and medium for quantitatively evaluating austenite stability of steel

    CN122063245B